Sequence of the clathrin heavy chain from Saccharomyces cerevisiae and requirement of the COOH terminus for clathrin function (The Rockefeller University Press, 1991)
The sequence of the clathrin heavy chain gene, CHC1, from Saccharomyces cerevisiae is reported. The gene encodes a protein of 1,653 amino acids that is 50% identical to the rat clathrin heavy chain (HC) (Kirchhausen, T., S. C. Harrison, E. P. Chow, R. J. Mattaliano, R. L. Ramachandran, J. Smart, and J. Brosius. 1987. Proc. Natl. Acad. Sci. USA. 84:8805-8809). The alignment extends over the complete length of the two proteins, except for a COOH-terminal extension of the rat HC and a few small gaps, primarily in the globular terminal domain. The yeast HC has four prolines in the region of the rat polypeptide that was proposed to form the binding site for clathrin light chains via an alpha-helical coiled-coil interaction. The yeast protein also lacks the COOH-terminal Pro-Gly rich segment present in the last 45 residues of the rat HC, which were proposed to be involved in the noncovalent association of HCs to form trimers at the triskelion vertex. To examine the importance of the COOH terminus of the HC for clathrin function, a HC containing a COOH-terminal deletion of 57 amino acids (HC delta 57) was expressed in clathrin-deficient yeast (chc1-delta). HC delta 57 rescued some of the phenotypes (slow growth at 30 degrees, genetic instability, and defects in mating and sporulation) associated with the chc1-delta mutation to normal or near normal. Also, truncated HCs were assembled into triskelions. However, cells with HC delta 57 were temperature sensitive for growth and still displayed a major defect in processing of the mating pheromone alpha-factor. Fewer coated vesicles could be isolated from cells with HC delta 57 than cells with the wild- type HC. This suggests that the COOH-terminal region is not required for formation of trimers, but it may be important for normal clathrin- coated vesicle structure and function.